The Future of Single-Frequency Integer Ambiguity Resolution - Verhagen, S; Teunissen, Peter; Odijk, D (Springer, 2012)
The coming decade will bring a proliferation of Global Navigation Satellite Systems (GNSSs) that are likely to enable a much wider range of demanding applications compared to the current GPS-only situation. One such important area of application is single-frequency real-time kinematic (RTK) positioning. Presently, however, such systems lack real-time performance. In this contribution we analyze the ambiguity resolution performance of the single-frequency RTK model for different next generation GNSS configurations and positioning scenarios. For this purpose, a closed form expression of the single-frequency Ambiguity Dilution of Precision (ADOP) is derived. This form gives a clear insight into how and to what extent the various factors of the underlying model contribute to the overall performance. Analytical and simulation results will be presented for different measurement scenarios. The results indicate that low-cost, single-frequency Galileo+GPS RTK will become a serious competitor to its more expensive dual-frequency cousin.